Question #07f4e

2 Answers
Nov 14, 2017

12,13,14

Explanation:

(12)+(13)+(14)=39
You know you need 3 integers that all have about the same value because they are consecutive, so divide 39 by 3.
393=13
You can then use 2 integers, one greater and one less than -13, to reach -39

Nov 14, 2017

12,13,14

Explanation:

Given: three consecutive integers with sum of -39

We know that the integers are consecutive, so let
x1=1st integer
x=2nd integer
x+1=3rd integer

Since we know that the sum of the three integers is -39, we know that
(x1)+(x)+(x+1)=39

Solving for this:
(x1)+(x)+(x+1)=39
x1+x+x+1=39
3x=39
x=13

In this case, by substituting the computed x with the values above, we would know that:
1st integer = -14
2nd integer = -13
3rd integer = -12

*Note that it does not matter if you add positive 1 or negative 1 just as long as you use consistent terms and you define your variables properly. So regardless of whether you use x, x - 1, x - 2 to define your three integers or x, x + 1, x + 2, you will still arrive at the same answer.